Economic Evaluation of Innovative Hair Restoration Services for Clients with Alopecia as a Direction for Diversification of Salon Business - Romaniuk, Maryna (Здобутки економіки: перспективи та інновації, 2025)
The relevance of the study is due to the growing demand for personalized and safe solutions in the field of aesthetic care, in particular for clients with alopecia. Against the backdrop of high competition and standardization of the salon services market, innovative hair restoration technologies are considered as a factor of long-term diversification and the formation of highly specialized services with high added value. The purpose of the article is to provide an economic justification for the feasibility of introducing innovative hair restoration services for clients with alopecia as a promising area for the development of the salon business, taking into account modern technological solutions, the characteristics of the target audience and practical experience in implementing the author’s methods in the field of medical and aesthetic services. The study used general scientific and applied methods: analysis and synthesis to study the state of innovation in the beauty industry; comparative analysis to assess the advantages of the author’s methods over traditional solutions; economic modeling to calculate the profitability of services; structural and logical generalization to formulate conclusions and recommendations. It has been established that innovative hair restoration services can provide stable profitability (60-75%) with moderate investment and trained staff. It is proved that the author’s SensHair and Nanoker techniques are in high demand among vulnerable categories of clients and contribute to the formation of long-term service relationships. The key barriers to development are identified - staff shortage, lack of standards, low level of consumer awareness. It is established that the successful integration of such services requires a systematic approach: from the development of training programs to the creation of a service model adapted for long-term interaction with clients. The expediency of implementing the author’s solutions in the practice of medical and aesthetic rehabilitation is confirmed. The author outlines areas for further research, in particular, the development of a regulatory framework, digital tools for evaluating efficiency, and a study of the impact of niche services on the economic sustainability of small businesses in the beauty industry.